Influence of graphene and copper on the photocatalytic response of TiO2 nanotubes. (1st March 2020) - Zghab, E.; Hamandi, M.; Dappozze, F.; Kochkar, H.; Zina, M. Saïd; Guillard, C.; Berhault, G.
Abstract: The photocatalytic properties of TiO2 nanotubes (NTs) modified by copper nanoparticles (NPs) and (reduced) graphene oxide ((r)GO) are herein evaluated. The hybrid TiO2 nanomaterials were deeply characterized by means of N2 adsorption-desorption measurements, X-ray diffraction, X-ray photoelectron and UV–vis diffuse reflectance spectroscopies, and transmission electron microscopy. On Cu/TiO2 NTs, results show a stabilization of Cu NPs at a +I oxidation state due to a strong interaction with TiO2 NTs leading to an 80% increase in activity for formic acid (FA) degradation under UV irradiation. Contrary to GO/TiO2 NTs, in the presence of Cu, addition of non-reduced GO leads to a 150% increase in activity compared to its free counterpart Cu/TiO2 NTs while the use of partially reduced GO leads to a complete loss of any beneficial effect due to graphene oxide.